2017
DOI: 10.1002/mabi.201700206
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin‐Rich Polyoxazoline–Poly(aspartic acid) Supramolecular Nanoparticles

Abstract: Cisplatin-rich supramolecular nanoparticles are constructed through the supramolecular inclusion interaction between the admantyl (Ad)-terminated poly(aspartic acid) (Ad-P(Asp)) and the β-cyclodextrin (β-CD)-terminated poly(2-methyl-2-oxazoline). In the formation of the nanoparticles, the β-CD/admantane inclusion complex integrates poly(2-methyl-2-oxazoline) and poly(aspartic acid) chains to form pseudoblock copolymers, followed by the coordination between carboxyl groups in P(Asp) block and cisplatin. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…As an example, Zhang et al prepared a supramolecular diblock copolymer by the complexation of PMeOx end-capped with β-cyclodextrin and adamantane end-functionalized poly(aspartic acid) (PAsp). [142] The PAsp block was crosslinked upon addition of the anticancer drug cisplatin, leading to stable micellar nanoformulation with very high drug loading (53 wt.%). The in vitro cytotoxicity of the formulation was observed in H22 cancer cells while an in vivo study in H22-bearing mice revealed increased tumor uptake of fluorescently labeled micelles, demonstrating their potential for anti-cancer therapy.…”
Section: Poly(dl-lactide) (Pla) Represents Another Hydrophobic Biodeg...mentioning
confidence: 99%
“…As an example, Zhang et al prepared a supramolecular diblock copolymer by the complexation of PMeOx end-capped with β-cyclodextrin and adamantane end-functionalized poly(aspartic acid) (PAsp). [142] The PAsp block was crosslinked upon addition of the anticancer drug cisplatin, leading to stable micellar nanoformulation with very high drug loading (53 wt.%). The in vitro cytotoxicity of the formulation was observed in H22 cancer cells while an in vivo study in H22-bearing mice revealed increased tumor uptake of fluorescently labeled micelles, demonstrating their potential for anti-cancer therapy.…”
Section: Poly(dl-lactide) (Pla) Represents Another Hydrophobic Biodeg...mentioning
confidence: 99%
“…There is an urgent need to develop new treatments for infections without risk of resistance [ 1 , 2 , 67 ]; the rapid and effective antimicrobial activity of AMPs makes them promising candidates [ 1 , 20 ]. In this study, we combined theoretical and experimental approaches to identify AMPs in H. illucens and to prepare and phenotypically test recombinant versions of these.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be necessary to investigate haemolytic activity (destroying red blood cells) and toxicity against eukaryotic cells as well as determining stability. Moreover, there has been recent interest in the use of H. illucens in the bioeconomy for bio-based processes and products e.g., food sustainability, waste reduction and as sustainable animal and fish feed [ 20 , 23 , 67 ]. We contend that H. illucens could be used to produce AMPs (e.g., Jg7904.t1), providing an environmental benefit from waste valorisation.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the unique in situ nontoxic to toxic antitumor mechanism and the good coordination of the Pt ion, many other nanostructures have been constructed and studied for cancer theranostic applications. [ 97 , 98 , 99 , 106 , 107 , 158 ] For future anticancer research work, a possible avenue to enhance cancer theranostic efficacy might entail tumor‐specific Pt release and induced formation of self‐assembled nanostructures with damage capability to cell DNA.…”
Section: Metal‐coordinated Supramolecular Self‐assemblies For Cancer Theranosticsmentioning
confidence: 99%